2011
DOI: 10.1155/2011/381787
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension Related to Left-Sided Cardiac Pathology

Abstract: Pulmonary hypertension (PH) is the end result of a variety of diverse pathologic processes. The chronic elevation in pulmonary artery pressure often leads to right ventricular pressure overload and subsequent right ventricular failure. In patients with left-sided cardiac disease, PH is quite common and associated with increased morbidity and mortality. This article will review the literature as it pertains to the epidemiology, pathogenesis, and diagnosis of PH related to aortic valve disease, mitral valve dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 65 publications
1
35
0
3
Order By: Relevance
“…Recent studies have established that an exaggerated increment in PAP during exercise is closely associated with impaired functional capacity in HF, 11 PAH, 12,49 exercise-induced PH, 12 and valvular heart disease. 37,62 Additional recent studies have shown that exercise PAP responses potently predict adverse outcomes in HF 11 and valvular heart disease 55,60,62,63 and also predict future PH progression in patients with COPD. 68 However, studies to date have been conducted in relatively small cohorts, using heterogenous exercise protocols, measurement methods, and definitions of abnormal hemodynamic responses to exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have established that an exaggerated increment in PAP during exercise is closely associated with impaired functional capacity in HF, 11 PAH, 12,49 exercise-induced PH, 12 and valvular heart disease. 37,62 Additional recent studies have shown that exercise PAP responses potently predict adverse outcomes in HF 11 and valvular heart disease 55,60,62,63 and also predict future PH progression in patients with COPD. 68 However, studies to date have been conducted in relatively small cohorts, using heterogenous exercise protocols, measurement methods, and definitions of abnormal hemodynamic responses to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…55 The presence of PH at rest or during exercise should therefore be included in perioperative risk assessment of mitral and aortic valve replacement. 56,57 In older patients with severe mitral valve stenosis and PH, the perioperative mortality increases to 20%; therefore, the indication of valve surgery has to be proven carefully.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…In our study, despite higher SPAP and increased prevalence of pulmonary hypertension among patients with super obesity, the presence of pulmonary hypertension, interestingly, was not independently associated with LVH. Several studies support the impact of increased weight on the development of breathing disorders and pulmonary hypertension [32]. It is well known that obesity-induced LV hypertrophy can promote LV diastolic dysfunction leading to pulmonary hypertension, but there is increasing evidence that metabolic syndrome, regardless of the presence of obstructive sleep apnea, can alter pulmonary hemodynamics [33].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, patients with PH secondary to mitral valve disease have been excluded from the clinical trials evaluating the current vasodilator therapies. 16 The patho- Note: Except where otherwise noted, data are mean value ± standard deviation. BW: birth weight; GA: gestational age; group 1: preterm infants with bronchopulmonary dysplasia (BPD); group 2: preterm infants with no BPD; group 3: term healthy infants; PDA: patent ductus arteriosus.…”
Section: Evidence From Adult Literaturementioning
confidence: 99%